Biomedical imaging : principles and applications - Salzer, Reiner, 1942- (Hoboken, NJ : John Wiley & Sons, 2012)
"This book presents and describes imaging technologies that can be used to study chemical processes and structural interactions in dynamic systems, principally in biomedical systems. The imaging technologies, largely biomedical imaging technologies such as MRT, Fluorescence mapping, raman mapping, nanoESCA, and CARS microscopy, have been selected according to their application range and to the chemical information content of their data. These technologies allow for the analysis and evaluation of delicate biological samples, which must not be disturbed during the profess. Ultimately, this may mean fewer animal lab tests and clinical trials"--Provided by publisher.
Evaluation of spectroscopic images -- Evaluation of tomographic data -- X-ray imaging -- Computed tomography -- Magnetic resonance tomography -- Toward a 3D view of cellular architecture: correlative light microscopy and electron tomography -- Tracer imaging -- Fluorescent imaging -- Infrared and Raman spectroscopic imaging -- Coherent anti-strokes Raman scattering microscopy -- Biomedical sonography -- Acoustic microscopy for biomedical applications.
Includes bibliographical references and index.
Print version record.
Keywords: Diagnostic imaging -- Digital techniques; Diagnostic imaging -- Handbooks, manuals, etc; Diagnostic Imaging; Spectrum Analysis; Medicine; Diagnostic imaging; MEDICAL -- Diagnosis; MEDICAL -- Diagnostic Imaging; Diagnostic imaging; Diagnostic imaging -- Digital techniques; Diagnostic imaging; Electronic books; Handbooks and manuals; Electronic books